1983
DOI: 10.1039/p29830000717
|View full text |Cite
|
Sign up to set email alerts
|

Acyl nitroxides. Part 4. Estimation of OH bond dissociation energies for N-t-butylhydroxamic acids

Abstract: E.s.r. spectroscopy has been used to determine the equilibrium constants for the hydrogen exchange reactions between N-t-butylhydroxamic acids and the stable piperidine N-oxyl (1) ; since the 0-H bond strength in (1)-H is known, this gives an estimate of the 0-H bond strengths in the hydroxamic acids. These are found to be stronger than those in dialkyl nitroxides and increase with increasing electron demand in the acyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Although one might expect the BDE of (PhCO)( t -Bu)NOH to be larger than that of (CF 3 ) 2 NOH, the actual BDE of PhCON( t -Bu)OH (323 kJ mol -1 ) is smaller than that of (CF 3 ) 2 NOH (346 kJ mol -1 ), which is reflected in the difference of the rate constants for hydrogen abstraction reactions from toluene. Jenkins et al measured the π-spin density on oxygen in 17 O-labeled (PhCO)( t -Bu)NO• and found that 12% of the π-spin exists on the carbonyl oxygen. , We are not sure how much π-spin exits on the carbonyl oxygen of the PINO radical. However, the two acyl groups of PINO• would delocalize the nitrogen lone pair to a greater extent than on the (PhCO)( t -Bu)NO•.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although one might expect the BDE of (PhCO)( t -Bu)NOH to be larger than that of (CF 3 ) 2 NOH, the actual BDE of PhCON( t -Bu)OH (323 kJ mol -1 ) is smaller than that of (CF 3 ) 2 NOH (346 kJ mol -1 ), which is reflected in the difference of the rate constants for hydrogen abstraction reactions from toluene. Jenkins et al measured the π-spin density on oxygen in 17 O-labeled (PhCO)( t -Bu)NO• and found that 12% of the π-spin exists on the carbonyl oxygen. , We are not sure how much π-spin exits on the carbonyl oxygen of the PINO radical. However, the two acyl groups of PINO• would delocalize the nitrogen lone pair to a greater extent than on the (PhCO)( t -Bu)NO•.…”
Section: Resultsmentioning
confidence: 98%
“…Jenkins et al proposed that lone-pair delocalization from nitroxide nitrogen would tend to fix the unpaired electron on oxygen. 38 Therefore, if the two acyl groups of NHPI withdraw electron density from the nitrogen atom and fix the unpaired electron on an oxygen atom (N-O•), this would strengthen the O-H bond of NHPI. However, if the unpaired electron exists principally on the carbonyl oxygen (structure III), we also must consider the π-spin density on the oxygen.…”
Section: Rate Constants Versus C-h Bond Dissociation Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in [23], the acyl groups of NHPI withdraw electron density from nitrogen atom and fix the electron on an oxygen atom in N-O, making the O-H bond stronger. Indeed, NHPLI contains three electron-withdrawing carbonyl groups and have the stronger O-H bond (90.25 kcal/ mol).…”
Section: Nhplimentioning
confidence: 85%
“…[13] [c] Ref. [16] asc.wiley-vch.de consisting of NHPI (10 mol %) and Co(acac) 2 , has been commercialized by the Daicel Chemical Company. The products are used in the manufacture of photoresistant polymers.…”
Section: ð2þmentioning
confidence: 99%